Experimental analysis of process parameters in semi-automatic blow molding of PET bottles: a case study at Universitas Negeri Malang product - Obaja Eden Sentosa Riyanto; Dewi Izzatus Tsamroh; Ilham Akbar Wandoyo; Den Arsyah Pilar Pancayudha; Hikmal Faidillah (Jurnal Polimesin, 2026)
This research aims to analyze the effects of key process parameters on product quality and defects in the semi-automatic blow molding of Polyethylene Terephthalate (PET) bottles at Malang State University (UM). The background of this study stems from the increasing demand for high-quality PET packaging and the limited number of direct experimental studies on semi-automatic machines, with a limited number of tests. Most previous studies have emphasized model-based simulation and optimization, while practical studies that observe the relationship between process parameters and defect characteristics remain rare. Unlike simulation-based studies, this work is based on direct field experiments under stable, industry-relevant machine settings to evaluate product quality and production readiness for mass manufacturing. The research method was conducted through direct experiments using 12.5 g PET preforms and a 330 mL capacity two-cavity mold. The main variables tested included preform temperature (70°C and 80°C), blow delay time (0.30–0.50 s), and low-blow duration (0.20–0.50 s). Bottle quality was evaluated based on thickness measurements, dimensions, and visual analysis of defects such as wrinkles, collapses, and wall irregularities. The results showed that a preform temperature of 80 °C and a low-blow duration of 0.50 s produced bottles of the highest quality, characterized by uniform wall thickness, flat bases, and minimal defects. In contrast, low-temperature settings (70 °C) resulted in high viscosity, leading to deformation and wrinkles. This optimal combination of parameters was proven to improve bottle structure homogeneity and reduce dimensional shrinkage to 1%. This study emphasizes the importance of temperature and blow time control in achieving stable, efficient, and mass-oriented PET bottle production, while strengthening the role of universities in experimental manufacturing applied research.